PERTANGGUNGJAWABAN PIDANA DALAM HUKUM PIDANA ISLAM - Zakaria Sayaf'i (Al Qalam, 2014)
Civil law violation is a form of a crime that is subjected to a certain sentence. This violation conducted by a person who is qualified to be a responsible according to law. Legal responsibility formed to identify whether a person is guilty or not qualified to be judged for his violation. In this case, if one is capable to be sentenced then it has to be cleared that the violations is legally violated. I In Islamic terminology legal responsibility also recognized. Both Islamic civil law and Indonesian state civil law are the same. However there are differences, in Islamic manner, legal responsibility objected to the formation of moral obligation, thus, every conduct that violated Shari’a will be subjected, however in an Indonesian civil law moral obligation is not to be considered. Keywords: hukum pidana, perbuatan pidana, pertanggungjawaban pidana